Specific Interventions for Stunting Management: Literature Review - Elba, Fardila (International Journal of Health Sciences, 2025)
Backgroundd : The prevalence of stunting in Indonesia has basically decreased every year, but the figure is still far above the limit set by WHO, which is below 20%. Based on the 2021 Indonesian Nutritional Status Study Indonesia's stunting prevalence rate is 24.4%. the purpose is to identify specific interventions for treating stunting Method: Study of literature from various electronic sources. Results: There are eleven specific interventions for treating stunting. Conclusion: The intervention includes four targets, starting with young women, pregnant women, toddlers and the community. These activities include screening for anemia, taking blood-boosting tablets, pregnancy checks antenatal care(ANC), consuming blood-boosting tablets for pregnant women, providing additional food for pregnant women with chronic energy deficiency monitoring toddler growth, exclusive breastfeeding, giving MP ASI rich animal protein for children under two, management of nutritional problems, increasing immunization coverage, education for pregnant women, adolescents and families including triggering open defecation.